Tajikistan's national epics - Aĭnī, Sadriddin, 1878-1954, author.
1 online resource.
Keywords: "Sadriddin Ayni (1878-1954) was a Tajik intellectual, regarded by many as one of the most important writers in the country's history. This book provides a translation of two historical monographs by Ayni: Is'yoni Muqanna (Muqanna's Rebellion) and Qahramoni Khalqi Tojik Temurmalik (The Tajik People's Hero Temur Malik). These works tell the story of two great Tajik heroes who fought against the Arabs and the Mongols. Besides the translations, the book discusses Ayni's life and work, highlighting his role, especially through these two monographs, in awakening and strengthening Tajik national consciousness. In addition, the book provides detailed background information on the historical events portrayed in the epics"--